Toward a Comprehensive, International and Interdisciplinary Analysis of Procreative Work - Hertzog, Irène-Lucile; Mathieu, Marie (Enfances, Familles, Générations, 2021)
Research Framework : In line with materialist feminist analyses, this paper revisits the boundaries between so-called productive versus reproductive work to deconstruct their foundations and show that, behind the social organization of procreation, there is work for which women are primarily responsible. Objectives : The purpose of this introduction is to examine the production of children and the decision not to have them through the lens of procreative work, thus integrating the different tasks involved in procreation, non-procreation and child rearing. This will also demonstrate the importance of thinking about the right to the work of procreation within the social norms that frame the multiple sequences of the (non)production of new human beings. Methodology : This introductory paper is based on a review of literature that clarifies the key concepts of “procreative work” and “procreative rights” that are used to analyze the tasks associated with procreation - understood in a broad sense – in order to contextualize the various papers in this issue. Results : While demonstrating the heuristic power of the conceptual choices made, the paper highlights areas of resistance to the analysis of procreative work and opens up multiple avenues of investigation to broaden this topic for a comprehensive, international and interdisciplinary understanding of the field of procreation. Conclusion : The interpretation proposed as a framework for thinking about the production of children and the decision to not have them, and what this implies for women, allows an array of everyday tasks that are particularly time-consuming and yet unnoticed to be brought to light. It highlights the need to integrate the different approaches, including legal norms, that constitute the social framework for procreative work. Contribution : This paper synthesizes knowledge regarding the concepts used to analyze tasks related to the (non)production of children.